INCULCATION OF EARLY CHILDHOOD RELIGIOUS MORALS IN LOVING AND CARING FOR ALLAH SWT'S CREATIONS IN NATURE KREASI EDUKASI KINDERGARTEN BANDAR LAMPUNG - Cahyani, S. Sekar Nur; Sulistianah, Sulistianah; Dewantari, T.; Herpratiwi, Herpratiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to describe the religious moral instillation of early childhood in loving and caring for Allah creation and to find out the factors that cause children to have the behavior of instilling religious morals in early childhood in loving and caring for Allah creation in Kindergarten Alam Kreasi Education Way Halim Bandar Lampung This research is a research using descriptive qualitative method. Sources of research data obtained from primary data and secondary data. The researcher obtained primary data from the results of interviews with school principals and class B teachers at Alam Kreasi Education Kindergarten and observations of children's behavior related to love for the school environment. Secondary data was obtained from the results of documentation, in the form of photos and videos of children's behavior towards the environment in Alam Kreasi Edukasi Kindergarten. The data obtained is then collected, reduced, described, tested for the validity of the data and concluded. The results showed that the inculcation of religious morals in early childhood at the Alam Kreasi Edukasi Kindergarten, Way Halim Bandar Lampung at grade B level was going well. most of the children have shown that there are no children who do not yet have behavior that reflects the religious morals of early childhood in loving and caring for Allah creation. This behavior is shown in several actions, namely the child always takes care of the environment, cares, is honest, polite, respects the surrounding environment, maintains personal hygiene, helps care for plants and does not act rudely to animals at school.